Phytoplanktonic response to simulated volcanic and desert dust deposition events in the South Indian and Southern Oceans. Issue 7 (24th May 2022) - Geisen, Carla; Ridame, Céline; Journet, Emilie; Delmelle, Pierre; Marie, Dominique; Lo Monaco, Claire; Metzl, Nicolas; Ammar, Rawaa; Kombo, Joelle; Cardinal, Damien
Abstract: Contrasting concentrations of macronutrients and micronutrients induce different nutrient limitations of the oceanic productivity and shape the composition of the phytoplankton communities of the South Indian Ocean and Indian sector of the Southern Ocean. o assess the phytoplankton response to nutrient release by desert dust and volcanic ash aerosols in these distinct biogeochemical regions, we conducted microcosm incubation experiments. A dry or wet deposition of either dust from Patagonia or ash from the Icelandic volcano Eyjafjallajökull or dissolved nutrients (Si, Fe, N and/or P) were added to trace metal clean incubations of surface seawater collected from five stations. These deposition experiments enabled the measurement of the biological response along with solubility calculations of nutrients. Both types of aerosols alleviated the iron deficiency occurring in the Southern Ocean during austral summer and resulted in a 24–110% enhancement of the primary production, depending on the station. The release of dissolved silicon may also have contributed to this response, although to a lesser extent, whereas neither the dust nor the ash relieved the nitrogen limitation in the low‐nutrient and low‐chlorophyll area. Diatom growth was responsible for 40% to 100% of the algal biomass increase within the responding stations, depending on the region and aerosol type. The high particle concentrations that are characteristic of ash deposition following volcanic eruptions may be of equal or higher importance to phytoplankton compared to desert dust, despite ashes' lower nutrient solubility to the ocean.